Case Report ; Management of Chronic Periodontitis After 2 Months of Traffic Accidents - Heru Maksmara (Eduvest - Journal of Universal Studies, 2022)
The availability of domestic raw materials is gradually decreasing, while the need for energy sources is increasing. Therefore, it is necessary to have the availability of renewable energy sources, one of which is biomass. In this study, researchers will discuss the waste of sugarcane bagasse and orange peel which can be used as briquettes. Usually, these wastes are only used as animal feed, sometimes they are just thrown away. The goals and benefits expected by the author in this study are, to provide information that the manufacture of briquettes from bagasse and Pacitan orange peel can be used as an alternative fuel. So, it can be implemented to reduce fossil fuels, whose availability is getting less and less. In the study, the best results were on the adhesive variable 20% ratio 1:2 with a calorific value of 5,949,114 cal/gram, 9% moisture content, 9% ash content.